User interfaces for interactive control of physics-based 3D characters - Zhao, P.; van de Panne, M. (2005)
We present two user interfaces for the interactive control of dynamically-simulated characters. The rst interface uses an `action palette' and targets sports prototyping applications. When used online, the user selects from a palette of actions (e.g., stand, pike, extend) during an ongoing simulation. Actions are de ned in terms of a set of target joint angles for PD controllers or as feedback-based balance controllers. When used of ine, the timing of the key motion events can be adjusted manually or optimized automatically to produce desired outcomes. We demonstrate the action palette interface with simulations of platform diving, freestyle aerial ski jumps, and half-pipe snowboarding. The second interface explores the feasibility of using a game-pad to control a 13-link rigid body simulation of snowboarding for game applications. Unlike traditional video game play, the stunts accessible through our interface need not be preconceived by the game author and can emerge as the product of the physics, the terrain, and the player skill. We describe the control mapping and provide a mechanism to simplify balance control. We demonstrate the system using numerous snowboarding stunts